Scabies in a patient with localized dystrophic epidermolysis bullosa type Cockaine-Touraine. Case report. - Calista, D.; Brunelli, D.; Landi, G. (European Journal of Pediatric Dermatology, 2018)
The Authors report a case of Sarcoptes scabiei var. hominis infestation in a patient with localized dystrophic epidermolysis bullosa type Cockayne-Touraine. The diagnosis was not difficult due to the presence of typical lesions on the trunk and upper limbs. However, in the extensor aspect of the legs, affected by the genetic disorder, due to the constitutional skin brittleness, the infestation was responsible for eroded and bullous lesions, that were reminiscent of the typical lesions of epidermolysis bullosa. The skin lesions of the trunk and upper limbs regressed after a 10-day therapeutical course. On the other hand, in spite of the negative result of the direct microscopic examination, the skin of the extensor aspect of thc legs turned to normal only after 4 months.